THE Most Important Book about Climate Change. Unsettled: What Climate Science Tells Us, What It Doesn’t, and Why It Matters by Steven E. Koonin - Bauer, Henry (Journal of Scientific Exploration, 2022)
If you want to know the facts about global warming and climate change, if you want to reach your own informed opinion about what should be done about it, this is the book to read. All relevant facts are presented clearly, very much including the historical records together with scrupulous citing of primary sources, among which the official published reports, international and national, feature prominently. The author’s credentials for this work could hardly be more impressive. Steven Koonin has been a successful physicist, including pioneering work on the use of high-performance computers in simulation and modeling. He gained some insights from the administrative role of Vice President and Provost at Caltech; another highly relevant experience as Chief Scientist for the oil company BP, focusing on renewable energy possibilities; and he was an Undersecretary for Science in the Department of Energy in the Obama Administration, focusing on energy technologies and climate science. He understands the viewpoints of scientists, of government, and of industry; in other words, he knows whereof he speaks. Throughout the book, Koonin takes deliberate, explicit care to write dispassionately and factually. At the outset, he acknowledges that the path to convincing any wide audience calls for arousing emotion, so that scientists are inevitably in a dilemma: whether simply to describe the facts and hope for appropriate attention to them, or whether to find emotionally impressive ways of spinning and hyping the facts. Koonin takes the first course quite effectively. For example, “the science doesn’t support what’s portrayed in most popular discussions” might also have been expressed as, say, “We are being massively misled about so-called climate science, by media, pundits, and official climate scientists.” Thus the book’s careful, factually based wording may easily seem incongruous as it describes unwarranted and unscrupulous mis-stating of facts, spinning, and hyping, which seem to be an integral part of official “consensual” “climate science,” to which the book refers as “The Science” to contrast with actual evidence-based science.